Error disclosure and family members' reactions: Does the type of error really matter?. Issue 4 (April 2015) - Leone, Daniela; Lamiani, Giulia; Vegni, Elena; Larson, Susan; Roter, Debra L.
Highlights Mentioning the error and apologizing seemed not to be common practice. The type of error (clear vs shared responsibility) affected the practice of disclosure. Communicating medical errors elicits strong negative emotions by patients. Specific training programs to improve disclosure practice should be implemented.